1996
DOI: 10.1161/01.atv.16.11.1319
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable State in Patients With Antiphospholipid Syndrome Is Related to High Induced Tissue Factor Expression on Monocytes and to Low Free Protein S

Abstract: Antiphospholipid antibodies (aPLs) are associated with thrombosis, but the mechanisms of this thrombotic tendency are unknown. We studied 56 patients 612 with systemic lupus erythematosus [SLE] and aPLs and previous thrombosis, 12 with SLE and aPLs but no thrombosis, 15 with SLE without aPLs or thrombosis, 11 with primary antiphospholipid syndrome with thrombosis, and 6 asymptomatic subjects with aPLs) to investigate the ability of aPLs to induce tissue factor (TF) expression on human normal monocytes. A doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 45 publications
3
74
0
1
Order By: Relevance
“…11 Simantov et al 22 recently showed that on adhesion of monocytes to ECs, adhesion molecule expression is enhanced in ECs and monocytes produce tissue factor. In our in vivo experiments, we have not eliminated the possibility that aPL may directly bind to monocytes via the Fc receptor and induce direct procoagulant activity in monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Simantov et al 22 recently showed that on adhesion of monocytes to ECs, adhesion molecule expression is enhanced in ECs and monocytes produce tissue factor. In our in vivo experiments, we have not eliminated the possibility that aPL may directly bind to monocytes via the Fc receptor and induce direct procoagulant activity in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators speculate that a prothrombotic state may be induced by aPL antibodies activating platelets 8 -10 or endothelial cells (ECs) or by inhibition of protein C activation. [11][12][13][14][15][16][17][18][19][20][21] aPL antibodies may bind phospholipids or ␤ 2 -glycoprotein 1 (␤ 2 GP1) in the membranes of ECs or platelets, resulting in their activation. 8 -10,16,22 EC activation by aPL antibodies has been demonstrated in vitro in several ways, including enhanced adhesion molecule expression and monocyte adherence 22,23 ; however, no in vivo studies have shown such activation.…”
mentioning
confidence: 99%
“…Kornberg and colleagues (32) induced a potent PCA activity resembling TF using human aCL MAb which previously induced APS. Reverter et al (33) described an increase of TF expression on healthy donor monocytes when incubated with plasma from antiphospholipid-positive SLE patients with thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…98 In one study, the ability of IgG to stimulate monocyte tissue factor expression was associated with the presence of decreased free protein S and increased prethrombotic markers. 99,100 Another means by which aPL antibodies may increase tissue factor activity and resultant Xa generation is via antibody-mediated inhibition of tissue factor pathway inhibitor activity. 101,102 Interference With the Components of the Protein C Pathway…”
Section: Induction Of Tissue Factor Activity By Leukocytesmentioning
confidence: 99%